PECULIARITIES OF CLASSIFYING AVIATION ENGINEERS ACCORDING TO THEIR SPECIALITIES IN GREAT BRITAIN - Korol, Liliya (Proceedings of National Aviation University (archive), 2017)
Introduction: The article deals with the issue of classifying aviation engineers in the system of higher education in Great Britain. Different ways of classification: There were considered both national classification and information sources available for future students. Types of aviation engineers: Joint Academic Coding System as well as jobs list available at Universities and Colleges Admissions Service were analyzed and three major groups of aviation engineers specializations were derived. Conclusions: We suggest that the results of the investigation should be used in further research of institutions that provide higher education for aviation engineers.